FASTING ON MONDAYS AND THURSDAYS AS A FACTOR INCREASES THE EMOTIONAL INTELLIGENCE OF YOUNG MOSLEM - Reza, Iredho Fani; Magfiroh, Magfiroh; Novianto, Andre; Ilham, Aripin; Ningsih, Eka Agustia; Pratiwi, Fegita Rahayu; Permatasari, Rezi Tiana (Jurnal Studia Insania, 2019)
Fasting is not only an obligation for a Moslem, but it also benefits the lives of Moslems who are fasting. This study examines the effectiveness of fasting Monday and Thursday toward emotional intelligence in young Moslems. This research is a kind of quantitative research experiment with the one-group pretest-posttest design model. The samples in this study have amounted to 15 young Moslems. The method of data collection uses the scale of emotional intelligence. The data analysis technique uses paired samples t-test techniques. The result of this study shows that fasting Monday and Thursday is one of the factors that increase emotional intelligence in young Moslems.